2011
DOI: 10.1007/s10903-011-9511-4
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Personal Risk About Smoking and Health Among Bosnian Refugees Living in The United States

Abstract: More than 60% of Bosnian refugees in the United States may be current smokers. Examining health beliefs can provide insight into smoking behaviors in this community. Four hundred ninety-nine Bosnians were interviewed about health beliefs and personal health risks related to smoking. ANOVA was used to compare current, former, and never smokers. General health beliefs were significantly different by smoking status with medium effect sizes (P < .001; η(2) = 0.04-0.06); current smokers were less likely to agree th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Harries and colleagues reported that current smokers were less likely to agree that smokers live shorter lives and that smokers are more likely to get heart disease. These smokers also perceived their own health risks as less severe than other smokers [36]. Another reason could be the association between perceived physical health risks and benefits of tobacco smoking and youth smoking status.…”
Section: Discussionmentioning
confidence: 99%
“…Harries and colleagues reported that current smokers were less likely to agree that smokers live shorter lives and that smokers are more likely to get heart disease. These smokers also perceived their own health risks as less severe than other smokers [36]. Another reason could be the association between perceived physical health risks and benefits of tobacco smoking and youth smoking status.…”
Section: Discussionmentioning
confidence: 99%
“…Large discrepancies on the prevalence of tobacco use were seen among the reviewed studies, ranging from 2.18% to 66.4% 41 56. These differences could be explained by the large variations of characteristics between the study populations, such as gender, age, ethnicity and geographic location.…”
Section: Discussionmentioning
confidence: 94%
“…The smoking prevalence recorded for adults ranged from 4.7% among female Albanian women in Kosovo to 66.4% among Bosnian refugees in the USA 41. For adolescents, the prevalence of smoking ranged from 2.2% for IDP adolescents in northern Uganda56 to around 70% for Israeli youth 43.…”
Section: Patterns Of Tobacco Usementioning
confidence: 98%
See 1 more Smart Citation
“…Given the results of this study, we can conduct further research to assess the applicability of a risk perception model to the smoking behavior of routine smokers in the target immigrant communities. The model has been shown effective in terms of modifying risk-taking behaviours, promoting positive perceptions, and improving self-efficacy that have been applied for changing smoking habits/behaviour among participants in different studies [33][34][35][36].…”
Section: Practical Implicationsmentioning
confidence: 99%